Analisis Kekuatan Struktur Bangunan Hotel Berdasarkan Respon Spektrum Terhadap Gaya Gempa di Kepulauan Riau Kota Batam Berdasarkan SNI 1726:2019 - Syakira Suci Maharani; Sapta Sapta; Sari Farlianti (Jurnal Multidisiplin Dehasen (MUDE), 2026)
His study discusses the structural design of a 13-story hotel building in Batam City, which effectively prevents structural failure due to earthquakes based on the Response Spectrum obtained for the Riau Islands, Batam City. The Special Moment Resisting Frame (SMRF) system is used in accordance with SNI 1726:2019. The building, measuring 55 × 21 meters with a height of 46 meters, utilizes concrete with a compressive strength of 30 MPa and reinforcing steel with a yield strength of 420 MPa. The objective of this study is to develop a reinforced concrete structural model for the 13-story hotel building that complies with the requirements of SNI 1726:2019 and to ensure the reinforced concrete design meets the provisions of SNI 2847:2019. This research employs the linear equivalent method with numerical and computational analysis to calculate the structural response under static-dynamic loading. The earthquake load analysis yielded vibration periods and frequencies of Tcx = 2.77 seconds and Tcy = 2.81 seconds, respectively. The maximum value of Cu·Ta obtained is 2.046, using T = 1.91 and T = 1.99. The performance results for the ultimate inter-story drift limits in the x and y directions are smaller than the allowable limit ∆s, indicating that the serviceability performance is safe.